Suspended Again: The Racialized Consequences of a 9th Grade Suspension on Future Suspension Patterns - Fisher, Benjamin W. (Race and social problems, 2022)
Although prior research has linked school-based punishment to a series of negative consequences, little is known about how being punished in school predicts future school-based punishment. To address this, the current study examines the extent to which being suspended in 9th grade predicts subsequent suspensions within the same school. Using stereotype congruence theory as a framework, we examine differences by race (black versus white) and household income. The data are drawn from three cohorts of four-wave annual administrative data from a large urban school district in the Midwestern USA (N = 11,006). Findings indicate that being suspended in 9th grade is associated with higher odds of subsequent suspension and a greater number of subsequent suspensions, but not a greater number of days per suspension. Black students suspended in 9th grade were particularly likely to experience more subsequent suspensions. Further, these racial differences are not driven by household income measures. These findings indicate that racially disparate school punishment practices have cascading effects for black students.